Conceptualising animation in rural communities: the Village SOS case. Issue 1 (1st January 2018) - McElwee, Gerard; Smith, Rob; Somerville, Peter
Abstract: This paper introduces and discusses the concept of animatorship in relation to rural enterprise and development. At its simplest level, animatorship is the art of animating others to achieve their objectives. We develop and apply this concept to understanding community development and community enterprise, with a specific emphasis on rural communities. We present a descriptive, conceptual study of a new concept i.e. animation in the context of entrepreneurship. The fieldwork for this paper took the form of structured face-to-face interviews with community development workers in November-January 2015/2016. These workers actively stimulate, motivate and inspire others and orchestrate situations and people to bring about change through others, not merely doing things for them. They build environments and relationships in which people grow, directing and focusing energies to develop and empower people's emotional and social lives and relationships through patient, open listening and group conversation.